Deprivation and oral health: a review - Locker D (Blackwell Synergy, 2000)
The link between socioeconomic status and health, including oral health, is well established. The conventional measures of socioeconomic status used in these studies, such as social class and household income, have a number of weaknesses so that alternatives, in the form of area-based measures of deprivation, are increasingly being used. This paper reviews epidemiological research linking deprivation and oral health. Four types of study are identified and described: simple descriptive, comparative, analytic and explanatory. These studies confirm that deprivation indices are sensitive to variations in oral health and oral health behaviours and can be used to identify small areas with high levels of Key words: deprivation; oral health; need for dental treatment and oral health promotion services. As such, they are socioeconomic status likely to provide a useful administrative tool. In terms of research, the studies D. Locker, Community Dental Health demonstrate that these measures provide a ready way of controlling for socio- Services Research Unit, Faculty of Dentistry, economic status in studies examining the association between oral health and University of Toronto, Toronto, Ontario M5G 1G6, Canada other variables.